Anatomy of welfare reform evaluation: Announcement and implementation effects - Richard Blundell; Marco Francesconi; Wilbert van der Klaauw (Institute for the Study of Labor (IZA), 2011)
This paper formulates a simple model of female labor force decisions which embeds an in-work benefit reform and explicitly allows for announcement and implementation effects. We explore several mechanisms through which women can respond to the announcement of a reform that increases in-work benefits, including sources of intertemporal substitution, human capital accumulation, and labor market frictions. Using the model's insights and information of the precise timing of the announcement and implementation of a major UK in-work benefit reform, we estimate its effects on single mothers' behavior. We find important announcement effects on employment decisions. We show that this finding is consistent with the presence of short-run frictions in the labor market. Evaluations of this reform which ignore such effects produce impact effect estimates that are biased downwards by 15 to 35 percent.
urn:nbn:de:101:1-201111029363
Keywords: D10; J13; J22; 330; policy evaluation; in-work benefit; anticipation effects; labor market frictions; intertemporal substitution; Aktivierende Sozialhilfe; Reform; Ankündigungseffekt; Wirkungsanalyse; Weibliche Arbeitskräfte; Arbeitsangebot; Schätzung; Großbritannien